Chương I : Ôn tập và bổ túc về số tự nhiên

Nguyễn Thị Yến Nhi

( x -3) + ( x - 2 ) + ( x -1 ) +...+10 + 11 =11

Nguyễn Thị Thùy Trâm
17 tháng 3 2020 lúc 11:00

(x - 3) + (x - 2) + (x - 1) + ... + 10 + 11 = 11

(x - 3) + (x - 2) + (x - 1) + ... + 10 = 0

(x - 3) + (x - 2) + (x - 1) + 55 = 0

(x - 3) + (x - 2) + (x - 1) = -55

3x - (3 + 2 + 1) = -55

3x - 6 = -55

3x = -49

x = -49/3

Bình luận (0)
Nguyễn Lê Phước Thịnh
Thiếu tướng -
17 tháng 3 2020 lúc 11:20

Ta có: (x-3)+(x-2)+(x-1)+x+...+10+11=11

\(\Leftrightarrow x-3+x-2+x-1+x+1+2+3+4+5+6+7+8+9+10+11=11\)

\(\Leftrightarrow4x+60=11\)

\(\Leftrightarrow4x=-49\)

\(\Leftrightarrow x=\frac{-49}{4}\)(ktm)

Vậy: \(x\in\varnothing\)

Bình luận (0)

Các câu hỏi tương tự

Khoá học trên OLM của Đại học Sư phạm HN

Loading...

Khoá học trên OLM của Đại học Sư phạm HN